Peningkatan Kemampuan Pemecahan Masalah Matematika Dengan Pendekatan Teaching At Right Level (TARL) Kelas XI SMA Negeri 5 Medan - Salihin Salihin; Rika Kartika; Susanna Ronaria Harahap (Journal on Education, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential so that they have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, the nation and the state. The aim of this research is whether the Teaching at the Right Level (TaRL) learning strategy can improve students' mathematical problem solving abilities. The research method used was classroom action research (PTK) which was carried out at SMA Negeri 5 Medan involving 36 class XI-3 students as research subjects. Based on the research results, it can be concluded that the Teaching at the Right Level approach can improve students' problem solving abilities in mathematics with an increase in the percentage in Cycle I 47% and Cycle II 81%.